Pengaruh Jenis Pupuk Cair dan Diameter Pot pada Budidaya Selada (Lactuca Sativa,L) Secara Hidroponik - Ursulina Uto Keraf; Krisantus Tri Pambudi Raharjo (Fakultas Pertanian, Universitas Timor, 2019)
Lactuca sativa L., is a vegetable that is short-lived and can be grown in the lowlands or the highlands. Lactuca sativa L. has a green texture. Lactuca sativa L. has a delicious and crunchy taste and can be consumed immediately. The purpose of this study was to determine the effect of liquid fertilizer types and pot diameter on the growth and yield of lettuce in hydroponic cultivation, to obtain the optimal type of liquid fertilizer and pot diameter to increase the growth and yield of Lactuca sativa L. in hydroponic cultivation. The planting media used for hydroponics must meet the requirements, which must be light, porous and clean. Cultivation in hydroponic substrate systems for vegetable plants should use light media, one of which is husk charcoal. A study aimed at obtaining the optimal type of liquid fertilizer and pot diameter to increase the growth and yield of Lactuca sativa L. in hydroponic cultivation was carried out in the garden of the Faculty of Agriculture, University of Timor, TTU Regency using a 3x3 factorial completely randomized design (CRD) repeated 3 times. The first factor is the type of organic liquid fertilizer, namely: AB Mix (J1), guano tea (J2), and Gliricidia sepium leaf compost tea (J3). The second factor is the pot diameter, namely: 8.5 cm (D1), 18 cm (D2) and 23 cm (D3). The results showed that the interaction between the treatment of pot diameter and type of liquid fertilizer did not occur in all observation parameters, but the use of a pot diameter of 18 cm with Gliricidia sepium leaf compost tea increased yields higher in the observation of total plant fresh weight, stew fresh weight and yield fresh weight Lactuca sativa L. plant.